Answer: 12 + 5a = 9a + -12
Reorder the terms:
12 + 5a = -12 + 9a
Solving
12 + 5a = -12 + 9a
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-9a' to each side of the equation.
12 + 5a + -9a = -12 + 9a + -9a
Combine like terms: 5a + -9a = -4a
12 + -4a = -12 + 9a + -9a
Combine like terms: 9a + -9a = 0
12 + -4a = -12 + 0
12 + -4a = -12
Add '-12' to each side of the equation.
12 + -12 + -4a = -12 + -12
Combine like terms: 12 + -12 = 0
0 + -4a = -12 + -12
-4a = -12 + -12
Combine like terms: -12 + -12 = -24
-4a = -24
Divide each side by '-4'.
a = 6
Simplifying
a = 6
Step-by-step explanation: found it off of google